Dynamic systems theory and embodiment in psychotherapy research. A new look at process and outcome (2016)
In an attempt to cease from reducing the world and its phenomena to linear modeling and analytic dissection, Dynamic Systems Theories (DST) and Embodiment theories and methods aim to account for the complex, dynamic, and non-linear phenomena that we constantly deal with in psychology. For instance, a DST and Embodiment perspective can enrich psychology’s understanding of communicative processes both in clinical and non-clinical settings. In psychotherapy, research has shown that there are a number of common factors contributing to psychotherapy outcome, of which the therapeutic relationship is the most important one. These findings give communication a central role in the psychotherapy process. In the traditional view, the underlying model of understanding psychotherapy processes is that of a number of components summatively coming together enabling us to make a linear causal prediction. Yet, communication is inherently dynamic. A shift to viewing the communication process in psychotherapy as a field dynamic phenomenon helps us to take into account nonlinear phenomena, such as feedback processes within and between persons. We thus propose an embodied enactive dynamic systems view as a new theoretical and methodological perspective that can more realistically capture what happens among and between two persons in psychotherapy. This view is broader than that of most current models in psychotherapy research. DST and Embodied Enactive Approaches can offer solutions to the prevailing neglect of non-linear phenomena in Western science, to better account for the complex dynamics of reality, and to move to a more holistic level of analysis. DST and Embodied Enactive Approaches have developed not in a single discipline but in a joined movement based on various fields such as physics, biology, robotics, anthropology, philosophy, linguistics, neuroscience, and psychology, and have only recently entered clinical theorizing. The two new paradigms are presently triggering a rethinking of the therapeutic process by recognizing the embodied nature of psychological and communicative phenomena. Their integration opens up a promising scenario in the field of psychotherapy research, developing new, profoundly transdisciplinary, theoretical concepts, methodologies, and standards of knowledge. The notion of field dynamics enables us to account for the role of the communicational context in the regulation of intra-psychological processes, while at the same time avoiding the pitfalls of an ontologization of the hierarchy of systemic organization. Moreover, the new approach implements methodological strategies that can transcend the conventional opposition between idiographic and nomothetic sciences.